Efek Pemberian Ekstrak Daun Salam (Syzygium polyanthum L.) terhadap Parameter Darah Tikus Putih (Rattus norvegicus L.) yang Terpapar Kadmium Klorida (CdCl₂) - Ahyadiyani, R.; Tambunan, Efrida Pima Sari; Hutasuhut, Melfa Aisyah (Journal of Natural Sciences, 2025)
Cadmium is a non-essential, carcinogenic metal commonly found in the environment. It can enter the human body through food consumption and has the potential to disrupt physiological systems, including the hematopoietic system. Bay leaves (Syzygium polyanthum) contain various bioactive compounds such as flavonoids, tannins, saponins, alkaloids, and antioxidants, which play a role in neutralizing free radicals. This study aims to analyze the effect of ethanol extract of bay leaves on erythrocyte, leukocyte, platelet counts, hemoglobin levels, and hematocrit in white rats (Rattus norvegicus L.) exposed to cadmium chloride (CdCl₂). The study employed a completely randomized design (CRD) with 20 rats divided into five treatment groups: a negative control, a positive control (CdCl₂ 40 mg/kgBW), and three treatment groups receiving bay leaf extract at doses of 200, 300, and 400 mg/kgBW. The research procedures included phytochemical screening, antioxidant activity testing, and blood profile analysis. The obtained data were analyzed using one-way ANOVA, followed by Duncan's post hoc test if significant differences were found. The results showed that administration of ethanol extract of bay leaves was able to restore blood parameters in rats to normal levels, with an optimal dose of 400 mg/kgBW.